How Environment, Cognition, and Behavior Shape Doctoral Students’ Academic Career Intentions: Insights from a Comprehensive Study - Wanhe Li; Xiaohan Jiang (Behavioral Sciences, 2025)
Although career choice is a kind of individual behavior, as the gatekeeper of the discipline, doctoral students’ academic career intention reflects the attractiveness of the academic labor market and determines the sustainable development of academic careers. An analysis of data (N = 1322) from a survey among Chinese doctoral students reveals that (1) environmental factors, such as departmental atmosphere and advisor support, cognitive factors like academic interest and research self-efficacy, as well as behavioral factors including research engagement and publication rates, significantly promote doctoral students’ academic career intentions; (2) female doctoral students and those from prestigious institutions show stronger academic career aspirations; (3) the influence of interest factors on doctoral students’ commitment to an academic career is particularly pronounced, especially in the field of fundamental science; (4) a clear understanding of career paths positively moderates the effect of interest on academic career intentions. Within increasingly severe competition in the global academic labor market, it is necessary to provide more support for doctoral students who are willing to engage in academic careers by enhancing career planning guidance for doctoral students and supporting them in making rational career plans and adequate preparations.